DETERMINANTS OF FRAUD RISK: EVIDENCE FROM THE FRAUD HEPTAGON FRAMEWORK IN THE INDUSTRIAL SECTOR - Mohamad Zulman Hakim; Anif Yanuar Y.I; Faiz Dzikrullah; Chaerul Anam (PT. ZILLZELL MEDIA PRIMA, 2026)
This study, which is based on the Fraud Heptagon Theory, looks at how the risk of financial statement fraud in industrial sector companies listed on the Indonesia Stock Exchange (IDX) between 2021 and 2024 is affected by Financial Target, External Pressure, Ineffective Monitoring, Change in Auditor, Change in Director, CEO Picture Frequency, Greed, and Ignorance. The study employs a quantitative methodology to analyze secondary data from annual reports and financial statements using panel data regression using the Common Effect Model (CEM). The results show that all factors have a significant simultaneous impact on financial statement fraud. Ineffective monitoring has a major detrimental influence on financial statement fraud, while ignorance has a beneficial impact. There are no noticeable repercussions from financial targets, outside pressure, director and auditor changes, CEO picture frequency, or greed. The study concludes that the primary reasons of dishonest business activities are still insufficient oversight and a lack of understanding of corporate governance.